The Characteristics of Hypertension Patients at Puskesmas Waru, Pamekasan in 2018 - Kiki Mellisa Andria; Sri Widati; Ira Nurmala (Universitas Airlangga, 2021)
Background: Hypertension is a hidden threat since it often occurs without symptoms. Hypertension disease is the main cause of stroke and heart disease, which affects most of the world’s population. The prevalence of hypertension in developed countries is quite high by 37% while in developing countries by 29.9%. Purpose: To know the hypertension patients’ profile at Puskesmas Waru, Pamekasan on January to December 2018. Method: This research method used an observational descriptive-qualitative study with a case study research design. The sample was taken with total sampling method from 220 people. Results: Among 220 people, who was diagnosed by hypertension was mostly at 45-65 years old by 57.3% and female by 62.3%. For educational factors they mostly had junior high school education by 34.5%. Whereas for the occupational factor more often occured in housewives by 36.8%. Most of their main problems were headache by 41.8%. The most of hypertension diagnosed type is primary hypertension by 42% and Stage 2 hypertension by 55.4% then also followed by family comorbidity by 60%. Conclusion: The aging process in women creates the hormonal factors that trigger the occurrence of hypertension. This is because at the age of 45, blood vessels will start to narrow and become stiff. The lack of education causes the receiving process of information become not maximum so that it will impact on health status and one of the causes is due to the stress that is experienced by many housewives. Stress causes the headaches. Therefore, mostly hypertension patients have the headache. Most hypertension cases occur without any definite cause and with Stage 2 and the presence of family comorbidity due to genetic factors that influence it.